Digitalization of Academic Facility Maintenance from QR Code Reporting to Automated Scheduling - Gastiadi, Arya Fridayana; Kallista, Meta; Dinimaharawati, Ashri (eProceedings of Engineering, 2025)
This paper presents a comprehensive solution to improve the maintenance process of academic facilities at the TULT Building of Telkom University by shifting from a manual to a digital system. The traditional approach relied heavily on physical media, such as checklists and control cards, resulting in issues such as data loss, delayed reporting, and poor monitoring. The proposed digital monitoring system leverages modern web and mobile technologies, including Vue.js for the frontend, Express.js for the backend, PostgreSQL for the database, and Genetic Algorithms for technician scheduling optimization. This system enables real-time damage reporting via QR code scans and ensures preventive maintenance through automatic scheduling and notifications. Results from alpha testing showed a 100% feature success rate, while beta testing yielded positive user feedback regarding usability, interface design, and system responsiveness. This study demonstrates that digitalization significantly enhances maintenance efficiency and the quality of academic services. Keywords — maintenance system, genetic algorithm, QR code academic facilities, Vue.js.